Respuesta :
1.
y = x + 2 , y = -3x
Since both are equal to y we can set them equal to each other:
x + 2 = -3x
2 = -4x
-1/2 = x
Now we will substitute the value of x in one of the equation to find the value of the y:
y = x + 2
y = -1/2 + 2
y = 1.5
So the solution of the first system is (-0.5,1.5).
2.
y = x + 20 , y = 6x
Since both are equal to y, we can set them equal to each other:
x + 20 = 6x
20 = 5x
4 = x
Now we will substitute the value of x in one of the equations to find the y:
y = 6x
y = 6(4)
y = 24
So the solution for the second set of equations is (4,24).
Hope this helps :)
y = x + 2 , y = -3x
Since both are equal to y we can set them equal to each other:
x + 2 = -3x
2 = -4x
-1/2 = x
Now we will substitute the value of x in one of the equation to find the value of the y:
y = x + 2
y = -1/2 + 2
y = 1.5
So the solution of the first system is (-0.5,1.5).
2.
y = x + 20 , y = 6x
Since both are equal to y, we can set them equal to each other:
x + 20 = 6x
20 = 5x
4 = x
Now we will substitute the value of x in one of the equations to find the y:
y = 6x
y = 6(4)
y = 24
So the solution for the second set of equations is (4,24).
Hope this helps :)